Role of mineral flotation technology in improving bitumen extraction from mined Athabasca oil sands: I. Flotation chemistry of water‐based oil sand extraction1 . (16th February 2018) - Zhou, Joe; Li, Haihong; Zhao, Liyan; Chow, Ross
Abstract: The role of surface hydrophobicity in water‐based oil sand extraction is examined from the perspective of mineral flotation separation. Although anionic carboxylates (sulphonates) released from bitumen are helpful for charging bitumen and liberating bitumen from sand grains, their presence in oil sand slurries tends to make bitumen and bubbles less hydrophobic. In addition, solid hydrophobization under oil sand extraction conditions can occur through different mechanisms of carboxylate adsorption. It is the hydrophobized fine solids that present challenges for achieving a high bitumen recovery with a good froth quality, due to their competition with bitumen for attachment to bubbles. While chemisorption of carboxylates contributes to hydrophobization of heavy minerals present in oil sands, carboxylate adsorption activated by hydrolyzed metal cations alters silica and clays from hydrophilic to hydrophobic. Different adsorption mechanisms of calcium on silica, clays, and other minerals are analyzed to explain why fine solids of varying mineralogy in combination with calcium affect bitumen extraction differently. Metal ions that activate solid hydrophobization under oil sand extraction conditions are identified from dynamic attachment of solids from mature fine tailings (MFT) to bitumen. To mitigate the effect of fines on oil sand extraction, selective flocculation of fine solids is recognized as especially feasible for bitumen flotation recovery from oil sand middling streams. Future research in reducing or eliminating caustic addition, understanding the role of inorganic anions, and searching for feasible techniques for treating MFT based on different mineralogy and surface properties, are briefly discussed.